COMBINED EFFECT OF TRAINING IN HYPERTENSIVE, OVERWEIGHT, POST-ABLATION SYNDROME WOLFF-PARKINSON-WHITE ABOUT FACTORS THAT TRIGGER ATRIAL FIBRILLATION. (Fiep Bulletin - online, 2012)
Exercise training has been recommended as the main agent in the treatment of atrial fibrillation by reducing the weight, control high blood pressure and thus decrease its action. Aims to determine the effects of combined training program an individual with overweight, hypertension, post-ablation of Wolff-Parkinson-White on factors that trigger atrial fibrillation. The training was conducted over a period of 3 months, and the individual has undergone an aerobic and resistance training at moderate intensity. There was a good evolution of the individual with a reduction in BMI from 26.1 to 23.6. Blood pressure was observed during the whole period there has been a slight decrease to levels where significant, the individual did not feel ill during or after exercise. This concludes that the combined training and moderate intensity exercise but significant effect in reducing the weight and in controlling atrial fibrillation.
Keywords: Combined Trainin; Wolff-Parkinson-White syndrome; atrial fibrillation.